2000
DOI: 10.1007/s11664-000-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-temperature annealing on GaInP/GaAs HBT structures grown by LP-MOVPE

Abstract: We have investigated the effect of high-temperature annealing on device performance of GaInP/GaAs HBTs using a wide range of MOVPE growth parameters for the C-doped base layer. Carbon doping was achieved either via TMG and AsH 3 only or by using an extrinsic carbon source. High-temperature annealing causes degradation of carbon-doped GaAs in terms of minority carrier properties even at doping levels of p = 1 × 10 19 cm -3 . The measured reduction in electron lifetime and luminescence intensity correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Brunner et al investigated effects of thermal annealing on current gain and lifetime between intrinsic doping and CBr 4 doping. 20) They found that the current gain reduction for intrinsic doping was 70%, whereas it was 50% using CBr 4 doping. The growths using CBr 4 doping were conducted on temperatures from 540 to 600 C and V/III ratios from 2 to 12.…”
Section: The Origin Of Current Gain Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brunner et al investigated effects of thermal annealing on current gain and lifetime between intrinsic doping and CBr 4 doping. 20) They found that the current gain reduction for intrinsic doping was 70%, whereas it was 50% using CBr 4 doping. The growths using CBr 4 doping were conducted on temperatures from 540 to 600 C and V/III ratios from 2 to 12.…”
Section: The Origin Of Current Gain Degradationmentioning
confidence: 99%
“…High temperature annealing removes hydrogen from the base layer; however, it also degrades HBT performances. 17,20) This paper presents the dependence of the V/III ratio of the base layer on current gain at various annealing conditions. The results have demonstrated that the V/III ratio plays a key role in current gain and its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on thermal annealing effects on current gain [14,15]. However, the devices consisted of Si-doped GaAs sub-collector concentrations $5 Â 10 18 cm À3 .…”
Section: Thermal Stability Of Carbon-doped P-gaasmentioning
confidence: 99%
“…Carbon doping in p-GaAs up to concentrations of 1 Â 10 20 cm À3 is well established, and is used for the p-side of the tunnel junctions [1,2]. In contrast, the maximum achievable doping concentration in n-GaAs is known to be limited well below 1 Â 10 19 cm À3 [3].…”
Section: Introductionmentioning
confidence: 99%